2005
DOI: 10.1063/1.2140893
|View full text |Cite
|
Sign up to set email alerts
|

High emission current density microwave-plasma-grown carbon nanotube arrays by postdepositional radio-frequency oxygen plasma treatment

Abstract: Highly stable field emission current densities of more than 6A∕cm2 along with scalable total field emission currents of ∼300μA per 70μm diameter carbon nanotube (CNT)-covered electron emitter dot are reported. Microwave-plasma chemical vapor deposition, along with a novel catalyst sandwich structure and postdepositional radio-frequency (rf) oxygen plasma treatment lead to well-structured vertically aligned CNTs with excellent and scalable emission properties. Scanning electron and transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Indeed, this finding is consistent with the results reported by other researchers showing that oxygen improves the electronic emission properties of CNTs. 12,[28][29][30][31][32] The band associated with the O1s core level electrons is located at a relatively low binding energy (530.3 eV), that was recently attributed to the C ¼ O bond of quinoid groups. 33 In particular, within this group there is a functional group, called benzoquinone, which contains two oxygen atoms doubly bonded to carbon in terminal parts of the structure.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Indeed, this finding is consistent with the results reported by other researchers showing that oxygen improves the electronic emission properties of CNTs. 12,[28][29][30][31][32] The band associated with the O1s core level electrons is located at a relatively low binding energy (530.3 eV), that was recently attributed to the C ¼ O bond of quinoid groups. 33 In particular, within this group there is a functional group, called benzoquinone, which contains two oxygen atoms doubly bonded to carbon in terminal parts of the structure.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…CNT arrays (CNTAs) cold cathodes show low turn-on/threshold fields and high current emission density, and they are fabricated by thermal chemical vapor deposition (TCVD), plasma enhanced CVD (PECVD), and microwave PECVD (MWPECVD) techniques [11][12][13]. Screen-printing is another method to fabricate CNT emitters, by which the raw materials CNTs can be obtained independently.…”
Section: Introductionmentioning
confidence: 99%
“…15͒ has been used to alter the FE properties of CNT arrays by removing surface amorphous carbon impurities, 16,17 introducing defects, 15 and by modifying the work function of the surface of the CNTs. 12 Previous work has shown that O 2 impurities etch the base of the CNTs during FE characterization due to large contact resistances between the substrate and CNTs, resulting in an increase in threshold field. 18 Our previous work has revealed that polystyrene ͑PS͒-multiwall carbon nanotube ͑MWNT͒ composite films exhibit excellent FE properties ͑low threshold fields: 1.6 V / m͒ from the fracture surface at relatively low CNT concentrations ͑ca.…”
mentioning
confidence: 99%